Impact of Credit and Investment Resources on the Productivity of Agricultural Sector - Sakhno, Andrii; Polishchuk, Natalia; Salkova, Iryna; Kucher, Anatolii (European Journal of Sustainable Development, 2019)
The current state of financial provision of agriculture in Ukraine is generally unsatisfactory; therefore, the problem of financing the agrarian sector of the economy in the form of lending and investing appears. The purpose of the article is to assess the impact of external financial support of enterprises in the form of lending and investing on agricultural productivity, as well as an assessment of the risk of overdue loans in the regional section of the agrarian sector of the Ukrainian economy. It is investigated the dependence of income (proceeds) on sales of products, proceeding from the needs of agricultural lending in ensuring the efficiency of its economic activity. Thus, lending and investing in agriculture contributes to increasing sales volumes and revenue (sales) growth from sales, as well as stimulating the development of agrarian enterprises, but the correlation between the analyzed indicators is insignificant. The evaluation results indicate a significant risk of overdue loans to agrarian enterprises for all regions of Ukraine, due to low technical efficiency and high level of delinquency. Significant differentiation of regions according to the level of technical efficiency has been revealed, which may indicate significant reserves of its increase. At the same time, it was found that the interest rates on agricultural loans are not a decisive factor for delays in loans granted to enterprises. In order to improve the situation, it is necessary to increase the volume of external financing and the link density between the parameters: lending – investment – the growth of production and sales, which will allow the formation of a functioning environment, taking into account the possibilities of optimizing costs in each region of the state. Key words: risks, lending, investment, agriculture, risk assessment, agrarian enterprises.